Função social da empresa e da previdência social: a questão do “limbo jurídico” trabalhista previdenciário - Fernandes, Vanessa Carla Genaro (2024)
The present research aims to analyze the correlation between the social function of Social Security and the social function of the Company in the face of the social security labor “Legal Limbo”, as well as its correspondence with the Constitutional Principles that underlie the most important judicial decisions on the subject. We cover a brief history of Social Security Systems and the practical aspects of the social security labor “Legal Limbo”, with the harmful consequences of the divergence between the conclusions drawn by experts from the National Institute of Social Security and occupational doctors, or private individuals, regarding the health condition and ability to work of employees. The problem still concerns the lack of specific legislation and the understanding that has prevailed in the National Labor Courts. The work was carried out through bibliographic and jurisprudential research